Strengthening Ecological Wisdom through Creative Wayang Media Based on Lampung Folktales in Elementary School Literature Appreciation Learning - Andri Wicaksono (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This study aims to analyze the story Sidang Belawan as the foundation for creating innovative wayang to internalize ecological wisdom and as inspiration for the design of creative wayang oriented toward Lampung culture. The research employs a research and development methodology integrated with artistic creation using empirical methods. The findings indicate that the life philosophy narrated in Sidang Belawan highlights ecological wisdom values, emphasizing awareness of nature as a source of life for humanity. Furthermore, ecological wisdom serves as the basis for shaping the design and form of wayang, manifested in the shape of the gunungan (kayon) as a representation of ecosystems and environmental elements, both biotic and abiotic.